KOMPLIKASI PERSALINAN PADA IBU HAMIL YANG MENGALAMI RISIKO TINGGI - Nuraisya, Wahyu; Khodariyah, Ita (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2025)
Pregnant women with high risk can experience complications in labor, as a condition that can threaten the mother's life during the birth process. This emergency must be handled immediately, because if it is slow in handling it can result in maternal death. The purpose of this research was to determine the description of the incidence of labor complications in pregnant women with high risk at the Dukun Gresik Public Health Center. This research design is descriptive to describe the events that occur with a retrospective cohort approach, with a single variable or independent variable, namely the incidence of labor complications in pregnant women. The research was conducted at the Dukun Gresik Public Health Center, Population All mothers giving birth with a history of high risk whose data was recorded at the Dukun Gresik Public Health Center, 1 year data of 178 mothers. total sampling technique obtained a sample of 178 respondents. Data was taken on January 13-17, 2025 with medical record instruments. Using frequency and percentage distribution. Based on the results of the research from a total of 178 respondents, it was found that most respondents, 91 respondents (51.1%) did not experience complications and almost half of the respondents, 87 respondents (48.9%) experienced complications. The type of labor complications, the most were 28 respondents (15.7%) prolonged labor, then complications of premature rupture of membranes 26 respondents (14.6%). And the lowest complications were 2 respondents (1.1%) complications of infection. Prolonged labor is the most significant complication in the delivery process.